The Influence of Environmental Value and Institutional Intervention in Developing Green Entrepreneurship in Bali - l Wayan Santika; Satria Pramudana; Sedana Yoga; Esmi Damayanti; Wenta Pharamadita (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Growing environmental degradation and sustainability challenges have increased the importance of promoting environmentally responsible entrepreneurship. This study examines and explains the influence of institutional intervention in the distribution of green entrepreneurial behavior by using the integration of social marketing and the theory of planned behavior. The novelty of this study is to use institutional intervention as a moderating variable on the relationship between green entrepreneurial intention and green entrepreneurial behavior. The study used quantitative methods. The population of this study is entrepreneurs. The size of the sample used was 120 people with a purposive sampling method. The analytical technique used is structural equation modelling using SEM-PLS. The test results showed that environmental value significantly moderated the influence of attitude toward behavior, subjective norm, and perceived behavioral control toward green entrepreneurial intention. Institutional intervention significantly moderates the influence of green entrepreneurial intention on green entrepreneurial behavior. Green entrepreneurial intention significantly mediates the effect of attitude, subjective norm, and perceived behavioral control on green entrepreneurial behavior among entrepreneurs. In order to increase the number of green entrepreneurships, it is necessary to pay attention to social marketing intervention factors and environmental values to form green entrepreneurial behavior.